The Influence of Different Irrigation Solutions on the Color Stability of Several Calcium Silicate–Based Materials - Koray Yılmaz; Pelin Tüfenkçi; Mehmet Adıgüzel (Selcuk Dental Journal)
Background:To compare the color stabilities of wMTA Angelus, Biodentine, EndoSequence Root Repair Material, and BIO MTA+. Calcium silicate-based materials in response to the exposure to different irrigation solutions. Methods:Four groups of materials (4 samples in each) were involved in the present study. Each of materials was homogenously mixed and placed in each container.After the setting time, all of the samples colors before the contact with solutions were determined by using a spectrophotometer. Then one sample from each material was kept in each of 4 irrigation solutions for 24 hours: distilled water, 5.25% NaOCl, 2% chlorhexidine gluconate (CHX] and 17% ethylenediaminetetraacetic acid (EDTA]. At the end of this period, the samples were taken out of the solutions and the color measurements were repeated. Results:Among all the materials, the discoloration of distilled water group was found to be the lowest at statistically significant level. The discoloration when exposed to Biodentine and wMTA Angelus irrigation solutions was at clinically acceptable level when compared to ES and BIO MTA+. Conclusions:Biodentine and wMTA Angelus may be used by clinicians as an alternative when the esthetic concerns play dominant role.Keywords:BIO MTA+; Biodentine; wMTA Angelus; EndoSequence Root Repair Material; Color Stability;